External jugular central venous line with standard catheter - Udaquiola, Bernardo; El Ters, Escandor (Cirugía del Uruguay, 1997)
Authors describe a technical variety of externa/ jugular central venous access, using a standard catheter instead of the technique which employs a "J" catheter guide. Results in 48 patients are analysed and compared to international series; success was 93,8% with no complications.